Penanaman Karakter Religius Taat Beribadah Melalui Pembiasaan Pembacaan Juz ‘Amma Beserta Terjemahnya Bagi Siswa Kelas IV MIS Nurul Falah Kertasari - Hilmi Hibatulloh; Wiwin Windayanti; Tuti Puspitasari (Mathematics Education Study Program, 2025)
The habit of reading Juz 'Amma which is done regularly before starting learning activities is one method to improve students' religious and disciplined character. This study aims to describe: 1) Development of religious character through the practice of reading Juz 'Amma in MI; 2) Development of disciplined character through the practice of reading Juz 'Amma in MI; 3) Challenges faced in developing religious and disciplined character with the practice of reading Juz 'Amma in MI; 4) Solutions to overcome challenges in developing religious and disciplined character through the practice of reading Juz 'Amma in MI. The type of research conducted is qualitative. The informants in this study consisted of the principal, class teachers, and students. The data collection methods used were observation, interviews, and documentation. The findings of the study indicate that the development of religious and disciplined character through the practice of reading Juz 'Amma is carried out in the form of routine activities that include reading Juz 'Amma and praying together before learning activities begin. Elements of religious character that are instilled include belief, worship, religious knowledge, religious experience, and consequences. The elements of discipline character developed include rules, punishments, rewards, and consistency. The approaches applied are the halaqoh and individual approaches. Thus, this study concludes that the practice of reading Juz 'Amma can improve the religious character and discipline of MI students.